2014
DOI: 10.1021/ja5037258
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Accelerated ReaxFF Reactive Dynamics with Validation from Simulating Hydrogen Combustion

Abstract: We develop here the methodology for dramatically accelerating the ReaxFF reactive force field based reactive molecular dynamics (RMD) simulations through use of the bond boost concept (BB), which we validate here for describing hydrogen combustion. The bond order, undercoordination, and overcoordination concepts of ReaxFF ensure that the BB correctly adapts to the instantaneous configurations in the reactive system to automatically identify the reactions appropriate to receive the bond boost. We refer to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Thirdly, the reliability of the predictions could be improved by shifting the simulation temperatures towards practical pyrolysis conditions. This could be feasible with recently introduced software and hardware acceleration methods, such as the accelerated ReaxFF reactive dynamics (aARRDyn) (Cheng et al 2014), reactive parallel replica dynamics (RPRD) (Joshi et al 2013) and the GPU-accelerated version of ReaxFF (Zheng et al 2013). Together, the suggested extensions would constitute a ReaxFF-MD framework for predicting the primary reaction pathways of cellulose pyrolysis, the associated kinetics and the main features of the product spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the reliability of the predictions could be improved by shifting the simulation temperatures towards practical pyrolysis conditions. This could be feasible with recently introduced software and hardware acceleration methods, such as the accelerated ReaxFF reactive dynamics (aARRDyn) (Cheng et al 2014), reactive parallel replica dynamics (RPRD) (Joshi et al 2013) and the GPU-accelerated version of ReaxFF (Zheng et al 2013). Together, the suggested extensions would constitute a ReaxFF-MD framework for predicting the primary reaction pathways of cellulose pyrolysis, the associated kinetics and the main features of the product spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the work by Döntgen et al [18] and previous publications, [20,[22][23][24] the chemical species are identified by establishing an atom connectivity map and then using a search algorithm (e.g., depth first) to build molecular fragments. The identified species are represented using the canonical SMILES [35,36] notation, which guarantees the uniqueness of any species labeled.…”
Section: Detection Of Species and Reactionsmentioning
confidence: 99%
“…Despite the advances in identifying reaction species and rates from simulation data, [12][13][14][15][16][17][18][19][20][21][22][23][24] there is no established method for obtaining reaction mechanisms that can be used directly for engineering (kinetic) modeling. In a recent work by Döntgen et al, [18] a method for identifying reaction species and elementary reactions was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The first‐principles methods provide the data for parameter fitting. The Goddard's group has developed a reactive force field (ReaxFF) as shown in Eq. E = E bond + E over + E under + E valence + E pen + E torsion + E conjugated + E vdWaals + E Coulomb …”
Section: Model Potentialmentioning
confidence: 99%
“…A great amount of computational resource is required for the repetitive calculations, especially for crystal structures with large unit cells and low symmetry. Therefore, some works employed the empirical charge methods, such as the charge equilibration (Qeq) method and electron equilibration method to accelerate the charge calculations …”
Section: Model Potentialmentioning
confidence: 99%